Understanding Consumer Sentiments Towards Marketing: An Investigation in Indian Context - Sanjay K. Jain; Parul Goel
Consumers constitute one of the most important elements of marketing environment. Understanding their sentiments towards marketing practices is a sine qua non for the development of effective marketing strategies, thus garnering their patronage, and attaining improved business performance. Based on Gaski and Etzel$1 (Bs (1986) framework, the present study attempts to investigate consumer sentiments towards marketing in India and compare the results with those of consumers in select other countries. Analysis of the data collected through a survey of consumers located in Delhi and the NCR region reveals consumers to be holding moderately favourable opinion that business firms pursue customer-oriented business philosophy. As regards marketing mix elements, retailing/selling emerges as the element towards which consumers have expressed the most positive sentiments. Practices in relation to advertising and product come next in order of favourability in consumer perceptions. Pricing is the variable for which consumers appear holding the least favourable opinion. In overall terms, though the consumer sentiments towards marketing in India are found only moderately favourable, these turn out to be relatively much more favourable when compared with those of consumers in other countries.s